FOXO3 longevity genotype protects elderly men with late‐life hypertension from Alzheimer's disease – Kuakini Honolulu Heart Program. (20th December 2022) - Chen, Randi; Morris, Brian J; Donlon, Timothy A; Ross, G Webster; Willcox, Bradley J; Allsopp, Richard C; Nakagawa, Kazuma; Masaki, Kamal H
Abstract: Background: While studies have found that mid‐life hypertension increases risk of Alzheimer's disease (AD), the association of late‐life hypertension with AD is still unclear, FOXO3 genotype influences mortality risk from cardio‐metabolic diseases (CHD, diabetes, and hypertension). We hypothesize that FOXO3 genotype affects the risk that late‐life hypertension poses to development of AD. Method: The study involved 2, 688 Japanese‐American men (mean age: 77.0 ± 4.1, range 71‐92) from the Kuakini Honolulu Heart Program with FOXO3 rs2802292 genotype, and information on incident AD from 1991 to 2012. Late‐life hypertension was defined as SBP/DBP ≥ 160/95 or taking anti‐hypertensive medication. Here, FOXO3 longevity haplotype ( FOXO3‐LH ) comprised minor allele frequencies of rs2802292 ( G ), rs2253310 ( C ), rs2802288 ( A ), rs2764264 ( C ), rs9398171 ( C ), rs12212067 ( G ), and rs3800230 ( G ). The association of FOXO3 genotype with late‐life hypertension and incident AD was assessed using a Cox proportional hazard model. Result: During 21 years of follow‐up, 513 people were diagnosed with incident AD. Age‐adjusted incidence rates of AD among late‐life hypertensive subjects showed that those with the rs2802292 longevity genotype TG / GG had a lower incidence than those with genotype TT (21.58 vs 24.49 per 1, 000 person‐years; p = 0.038). A multivariable Cox model, adjusting for age, education, APOE‐ε4 and other CVD risk factors, showed late‐life hypertension protects men from AD only for those with a longevity genotype such as rs2802292 TG / GG (HR = 0.68, 95% CI 0.52–0.89; p = 0.0052), and with the FOXO3‐LH (HR = 0.59, 95% CI 0.39–0.91; p = 0.016), but this was not seen for the rs2802292 genotype TT (HR = 1.15, 95% CI 0.89–1.49; p = 0.28), nor in the absence of the FOXO3‐LH (HR = 1.14, 95% CI 0.88–1.49; p = 0.31). Conclusion: This study provides the first evidence that FOXO3 genotype influences the risk that late‐life hypertension has on developing Alzheimer's disease. Only with the FOXO3 longevity genotype was there protection against a late‐life hypertension‐mediated increase in incident AD risk. The findings have implications for the effect of the FOXO3 longevity genotype on late‐life hypertension‐associated risk of AD. Without considering the effect of FOXO3 longevity genotype, one should be cautious about generalizations concerning the protective effect of late‐life hypertension on AD in the population.